Biodiversity and scientific travelers: a vision from the Andes - Escobar-Mamani, Fortunato (2021)
The Andean region has always fascinated travelers and scholars who are interested in biodiversity. Monumental works have been written on mineral resources, flora and fauna. And efforts are being made to protect the richness of biodiversity, especially in protected natural areas. But the threats from the advance of extractive activities and the consequences of climate change are becoming more and more shocking and are avoiding the achievement of sustainable development. For this reason, the production of knowledge and its spread in quality scientific journals is an urgent need, based on data from reality itself and its resources, in light of the scientific literature produced. In this scenario, the Highlands Research Journal wishes to invite everyone to contribute with their proposals to face the challenge of environmental degradation, the exploitation of natural resources, the effects of climate change and the persistence of socio-environmental conflicts, of which it is essential to take into account social facts, in the search for possible solutions to achieve the balance between man and nature and guide activities towards the conservation, rational and sustainable use of natural resources. History is full of lessons that should not be forgotten, about the wealth of Andean natural resources and the enormous body of knowledge that traveling scientists have left us in recent centuries.